KUAT TEKAN BETON GEOPOLIMER DENGAN BAHAN UTAMA FLY ASH SEBAGAI PEMBENTUK PASTA - Syamsul Bahri Ahmad; Muh.Suradi (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
The concrete industry is currently the second largest user of natural resources in the world. Recently, an aggregate binder that does not use portland cement has been developed which known as geopolymer. The main component of this geopolymer is the presence of high SiO2 and Al2O3 compounds in industrial waste materials with alkaline NaOH or KOH solutions as polymerization activators. This study aims to analyze the compressive strength of geopolymer concrete with the main ingredient of fly ash as a geopolymer paste with the activator ratio of Na2SiO3 and NaOH is 2 at molarities of NaOH 8M, 12M, and 16M, then compare it with the compressive strength of conventional concrete using PCC cement. The research results show that the average concrete compressive strength (fcr) of conventional concrete, NaOH 8M, 12M and 16M geopolymer concrete is 22.21 Mpa, 9.37 Mpa, 11.89 Mpa and 13.10 Mpa respectively. The compressive strength of geopolymer concrete obtained is still lower than conventional concrete. This can be caused by the molarity value of NaOH and the activator ratio which require more variation.